2012
DOI: 10.1111/j.1365-277x.2012.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two pulmonary enteral formulations on nutritional indices and outcomes

Abstract: The use of a specialised pulmonary enteral formulation did not result in any statistically significant effects on ICU days and hours on mechanical ventilation. Subjects who were on the specialised formula did receive more enteral formula volume and more total energy intake, which may be clinically important. Further clinical studies are needed to address the impact that a specialised pulmonary enteral formula has on ICU stay and ventilator hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In total, 675 articles were retrieved, and 653 articles were excluded because of duplication and lack of relevance based on title and abstract screening. After careful screening of the full texts of the 27 trials, 17 articles were excluded for following reasons: (a) the article was commentary (n = 1) 29 ; (b) the study was the part of another study (n = 1) 30 ; (c) studies did not have defined outcomes (n = 2) 31,32 ; (d) full text was not available (n = 1) 33 ; (e) studies without sufficient data (n = 1) 34 ; (f) studies conducted in children (n = 4) 35‐38 ; (g) studies were not RCTs (n = 4) 39‐42 ; or (h) studies were not conducted on critically ill patients (n = 3) 43‐45 . In total, 10 RCTs (1166 participants) were eligible to be included in the present systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 675 articles were retrieved, and 653 articles were excluded because of duplication and lack of relevance based on title and abstract screening. After careful screening of the full texts of the 27 trials, 17 articles were excluded for following reasons: (a) the article was commentary (n = 1) 29 ; (b) the study was the part of another study (n = 1) 30 ; (c) studies did not have defined outcomes (n = 2) 31,32 ; (d) full text was not available (n = 1) 33 ; (e) studies without sufficient data (n = 1) 34 ; (f) studies conducted in children (n = 4) 35‐38 ; (g) studies were not RCTs (n = 4) 39‐42 ; or (h) studies were not conducted on critically ill patients (n = 3) 43‐45 . In total, 10 RCTs (1166 participants) were eligible to be included in the present systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…P values less than .05 were considered as statistically significant. (g) studies were not RCTs (n = 4) [39][40][41][42] ; or (h) studies were not conducted on critically ill patients (n = 3). [43][44][45] In total, 10 RCTs (1166 participants) were eligible to be included in the present systematic review and meta-analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…65 Although some researchers have reported that use of immune-enhanced pulmonary formulas, compared with standard controls, resulted in decreased inflammation, improved oxygenation, and reduced ventilator days, ICU length of stay (LOS), and incidence of new organ failure, 66-68 others conclude that use of EPA/GLA-enriched formulas does not improve ICU LOS or time on mechanical ventilation. 69 These patients, however, received approximately 1000-1200 kcal/d from the enteral formula, in addition to approximately 1000 kcal/d from propofol infusion, possibly leading to overfeeding, specifically from an ω-6-rich source (propofol). Initial studies reporting benefits of use of formulas high in ω-3 fish oil have been criticized for use of the standard EN formula with high proinflammatory ω-6 fatty acid content as a control, potentially leading to increased inflammatory response and confounding the outcomes in favor of the fish oil-containing formulas by way of administering a proinflammatory substrate that may have exacerbated the inflammatory response.…”
Section: Fish Oil/pulmonary Formulasmentioning
confidence: 99%
“…After careful screening of the full texts of the 27 trials, 17 articles were excluded for following reasons: article was commentary (n=1) (Schott and Huang, 2012), study was the part of another study (n=1) (Pacht et al, 2003), studies did not have defined outcomes (n=2) (Nelson et al, 2003, Theilla et al, 2007. Full text was not available (n=1) (Tang et al, 2008), studies without sufficient data (n=1) (Elamin et al, 2005), studies conducted in children (n=4) (Al-Biltagi et al, 2017, Covar et al, 2010, Hamilton and Trobaugh, 2011, Jacobs et al, 2013, articles were not RCT (n=4) (Cohen et al, 2013, Gadek et al, 1998, Lev and Singer, 2012, Pontes-Arruda, 2005), or were not conducted on critically ill patients (n=3) (Kalantar-Zadeh et al, 2005, Remans et al, 2004, Matsuda et al, 2017. In total, 10 clinical trials (1166 participants) were eligible to be included in the present systematic review and meta-analysis.…”
Section: Included Studiesmentioning
confidence: 99%